PROVERBS AND SAYINGS AS A REFLECTION OF NATIONAL CHARACTERISTICS OF THE PERCEPTION OF THE WORLD (Scientific journal of the Fergana State University, 2023)
The article is devoted to the analysis of features of proverbs and sayings of English, their national origin and approaches to their definition.